Experimental study on anti-icing and deicing performance of polyurethane concrete as road surface layer. (10th February 2018) - Chen, Jun; Ma, Xie; Wang, Hao; Xie, Pengyu; Huang, Wei
Highlights: Measured thermal properties of polyurethane concrete and asphalt concrete. Conducted pull-off test and inclined shear test of ice-concrete interface and ice rupture test. Compared ice formation time of polyurethane concrete and asphalt concrete. Proved polyurethane concrete having superior deicing and anti-icing performance. Abstract: This study aims to investigate deicing and anti-icing performance of an innovative pavement surface layer that replaces asphalt binder with polyurethane using laboratory tests. The ice-mixture composite specimens were prepared using asphalt binder and polyurethane with the same aggregate type and gradation. The deicing and anti-icing performance of polyurethane concrete at different freezing time was compared to the traditional asphalt concrete. It was found that polyurethane concrete has similar thermal conductivity but much greater specific heat as compared to asphalt concrete. Compared to asphalt concrete, polyurethane concrete can significantly retard the ice-formation time. The pull-off strength and interface shear strength at the interface of ice and polyurethane concrete is about 50% and 55% of those at the interface of ice and asphalt concrete. The work of rupture to break ice layer on polyurethane concrete is about 50% of the work required on asphalt concrete with the same ice layer thickness. The findings demonstrate the potential of using polyurethane concrete on roadways in cold regions to provide better anti-icing and deicing performance and enhance traffic safety at winter seasons.